1997
DOI: 10.1901/jaba.1997.30-439
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Reinforcer Preference as a Function of Schedule Requirements and Stimulus Similarity

Abstract: Tustin (1994) recently observed that an individual's preference for one of two concurrently available reinforcers under low schedule requirements (concurrent fixed-ratio [FR] 1) switched to the other reinforcer when the schedule requirements were high (concurrent FR 10). We extended this line of research by examining preference for similar and dissimilar reinforcers (i.e., those affecting the same sensory modality and those affecting different sensory modalities). Two individuals with developmental disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 13 publications
7
77
1
Order By: Relevance
“…Based on these findings, DeLeon et al (1997) suggested that increased schedule requirements may magnify small differences in preference between similar but not dissimilar stimuli. This is because stimuli that share physical characteristics (e.g., food items) are more likely to share functional properties as well (e.g., hunger reduction).…”
Section: Choice and Reinforcer Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, DeLeon et al (1997) suggested that increased schedule requirements may magnify small differences in preference between similar but not dissimilar stimuli. This is because stimuli that share physical characteristics (e.g., food items) are more likely to share functional properties as well (e.g., hunger reduction).…”
Section: Choice and Reinforcer Assessmentsmentioning
confidence: 99%
“…However, two recent applied investigations (DeLeon, Iwata, Goh, & Worsdell, 1997;Tustin, 1994) based on principles of behavioral economics illustrate how schedule density may affect an individual's preferences for two concurrently available reinforcers. However, two recent applied investigations (DeLeon, Iwata, Goh, & Worsdell, 1997;Tustin, 1994) based on principles of behavioral economics illustrate how schedule density may affect an individual's preferences for two concurrently available reinforcers.…”
Section: Choice and Reinforcer Assessmentsmentioning
confidence: 99%
“…Correspondingly, investigations with persons with developmental disabilities have concerned the relative effectiveness of reinforcers as a function of their unit price or related economic variables (DeLeon, Iwata, Goh, & Worsdell, 1997;Delmendo, Borrero, Beauchamp, & Francisco, 2009;Kodak, Lerman, & Call, 2007;Reed et al, 2009;Roane, Call, & Falcomata;2005). Among other contributions, behavioral economic analyses have provided a systematic means for investigating and quantifying relative value among qualitatively dissimilar reinforcers, sometimes by examining these relations when the reinforcers are concurrently available.…”
Section: Implications Of Behavioral Economicsmentioning
confidence: 99%
“…Differential reinforcement . Behavioral assessment A progressive ratio (PR) schedule of reinforcement is defined by an increasing response requirement for reinforcer delivery over successive sessions (DeLeon et al 1997), or trial-by-trial basis within a single session (Hodos 1961;Roane 2008). For instance, when a child emits a predetermined number of responses (e.g., hand raising five times in a classroom), a reinforcer is delivered (e.g., teacher calls on child).…”
mentioning
confidence: 99%
“…After delivery of the reinforcer, subsequent response requirements can increase a variety of ways, including stepwise (e.g., increasing the number of responses from 5 to 6, then 7, then 8, and so forth), algorithmic (e.g., additively or geometrically), response topography (e.g., specific target response either occurs or stops occurring), session-termination criteria (e.g., specific amount of time elapses between responses, or after a total amount of time elapses within the session), and the amount of reinforces delivered (see also Roane, 2008 for similar overview). Stepwise increases in response requirements have been useful in identifying preference for stimuli used as reinforcers across increased response requirements (Tustin 1994;DeLeon et al 1997), and reinforcer efficacy across differentiated response requirements (Roane et al 2001).…”
mentioning
confidence: 99%